2010
DOI: 10.1159/000318746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Selective Cyclooxygenase-2 Inhibitor Celecoxib in the Treatment of Rheumatoid Arthritis and Osteoarthritis in Japan

Abstract: Background/Aims: Gastrointestinal (GI) disorders are common adverse reactions of nonsteroidal anti-inflammatory drugs (NSAIDs). Loxoprofen is a representative NSAID widely used in East Asia. A selective cyclooxygenase-2 inhibitor, celecoxib, was introduced in Japan in 2007. In this study, we aimed to compare the efficacy and safety of celecoxib with those of loxoprofen in Japanese patients. Methods: We analyzed the data from 12 clinical studies conducted in Japan. These data of Japanese patients were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 157 publications
(79 reference statements)
1
22
0
Order By: Relevance
“…All remaining subjects were then randomized, by a computer-generated randomization system, to receive either celecoxib (200 mg twice daily) or meloxicam (10 mg once daily) for 2 weeks. The dose of each drug was determined on the basis of the dose approved by the Japanese Ministry of Health and Welfare and applied to other clinical trials [24,25]. In both groups, omeprazole (20 mg once daily) was given in consideration of possible gastric mucosal injury.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All remaining subjects were then randomized, by a computer-generated randomization system, to receive either celecoxib (200 mg twice daily) or meloxicam (10 mg once daily) for 2 weeks. The dose of each drug was determined on the basis of the dose approved by the Japanese Ministry of Health and Welfare and applied to other clinical trials [24,25]. In both groups, omeprazole (20 mg once daily) was given in consideration of possible gastric mucosal injury.…”
Section: Methodsmentioning
confidence: 99%
“…In the meloxicam group, two subjects experienced abdominal discomfort and one subject had diarrhea. As shown in Table 2, the GSRS score was 17 (range [15][16][17][18][19][20][21][22][23][24][25] in the celecoxib group and 18 (range [15][16][17][18][19][20][21][22][23][24][25][26] in the meloxicam group. None of the subjects manifested anemia at the end of the medication period.…”
Section: Symptoms Laboratory Data and Complicationsmentioning
confidence: 99%
“…An analysis of 12 studies that compared celecoxib with loxoprofen in Japanese patients with OA or rheumatoid arthritis (RA) showed that there were significantly fewer serious GI events, including symptomatic ulcers, with celecoxib ( P  <   0.05) 20. An analysis of three 12‐week studies that compared twice‐daily celecoxib with diclofenac in Chinese patients with OA or RA showed that there was no statistical difference in occurrence of gastroduodenal ulcers (primary outcome) (2.8% vs .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, COX-2 selective inhibitors have been developed as NSAIDs with fewer adverse effects and applied in the clinical setting. Celecoxib is a typical COX-2 inhibitor and several studies have reported that it causes fewer adverse effects such as gastrointestinal disorders or renal disorders compared with conventional non-selective COX inhibitors such as ibuprofen, loxoprofen, naproxen, or diclofenac [5][6][7][8][9][10]. Celecoxib was approved and came to market in the USA in 1999 with indications and usage for osteoarthritis, rheumatoid arthritis, ankylosing spondylitis, acute pain, and primary dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%